2009
DOI: 10.1101/gad.1809309
|View full text |Cite
|
Sign up to set email alerts
|

A developmentally regulated inducer of EMT, LBX1, contributes to breast cancer progression

Abstract: Epithelial-to-mesenchymal transition (EMT) plays an important role during normal embryogenesis, and it has been implicated in cancer invasion and metastasis. Here, we report that Ladybird homeobox 1 (LBX1), a developmentally regulated homeobox gene, directs expression of the known EMT inducers ZEB1, ZEB2, Snail1, and transforming growth factor β2 (TGFB2). In mammary epithelial cells, overexpression of LBX1 leads to morphological transformation, expression of mesenchymal markers, enhanced cell migration, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 28 publications
6
73
0
Order By: Relevance
“…Developmental EMT regulators including Twist1, Twist2, Snai1, Slug and Six1, as well as developmental signalling pathways, including TGF-b and Wnt/b-catenin, are aberrantly activated in cancers and correlate with poor clinical outcomes. Recently, EMT inducers or regulators, such as Twist1, Snai1, TGF-b, ZEB1, YB-1, LBX1 and Six1, have been shown to induce well-differentiated cells and cancer cells to form populations with stem celllike characteristics via promoting EMT, indicating that there is a cross-talk between the EMT programme and the pathways involved in regulating stemness in stem cells Morel et al, 2008;Evdokimova et al, 2009;Iliopoulos et al, 2009;McCoy et al, 2009;Polyak and Weinberg, 2009;Wellner et al, 2009;Yu et al, 2009;Ouyang et al, 2010;Singh and Settleman, 2010). In this study, we demonstrated that Twist2 has a critical role in EMT and is involved in reprogramming differentiated cells and cancer cells into stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental EMT regulators including Twist1, Twist2, Snai1, Slug and Six1, as well as developmental signalling pathways, including TGF-b and Wnt/b-catenin, are aberrantly activated in cancers and correlate with poor clinical outcomes. Recently, EMT inducers or regulators, such as Twist1, Snai1, TGF-b, ZEB1, YB-1, LBX1 and Six1, have been shown to induce well-differentiated cells and cancer cells to form populations with stem celllike characteristics via promoting EMT, indicating that there is a cross-talk between the EMT programme and the pathways involved in regulating stemness in stem cells Morel et al, 2008;Evdokimova et al, 2009;Iliopoulos et al, 2009;McCoy et al, 2009;Polyak and Weinberg, 2009;Wellner et al, 2009;Yu et al, 2009;Ouyang et al, 2010;Singh and Settleman, 2010). In this study, we demonstrated that Twist2 has a critical role in EMT and is involved in reprogramming differentiated cells and cancer cells into stem-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…MCF-10A cells are immortalised, non-transformed human mammary epithelial cells, and do not show capabilities of transforming and tumour growth even with ectopic overexpression of oncogene K-Ras, HRas V12 or LBX1 Yu et al, 2009). Therefore, we used MCF-7 cells ectopically expressing Twist2 to determine the effects of Twist2 expression on cell migration and colony-forming activity in vitro and on tumourigenicity in nude mice.…”
Section: Twist2 Induces Emt In Mammary Epithelial Cells and Breast Camentioning
confidence: 99%
“…An observational study utilizing human breast cancer specimens quickly followed and indicated that CSCs isolated from breast cancer display a distinct EMT signature [145]. More recently, LBX1, which directs expression of Snail, Zeb1 and Zeb2, was also noted to expand the CD44+CD24-CSC subpopulation and to morphologically transform mammary epithelial cells [146]. Finally, in the setting of head and neck cancer, Yang et al provided convincing evidence that Twist1 directly regulates the stemness factor Bmi1 via cooperative repression of E-cadherin and p16 INK4a .…”
Section: Inflammation-inducible Emt Drives Stemness and Contributes Tmentioning
confidence: 99%
“…56,57 It binds transcription factors, such Zeb1/2, Twist1/2 and Ladybird homeobox 1 (LBX1). 32,[36][37][38] Activation of the EMT program enables transformed epithelial cells to invade locally, to disseminate via blood or lymphatic vessels and to establish micrometastasis. 34,35 Thus, EMT may account for major steps in the metastatic cascade, with the exception of growth at the secondary site.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%